Research on visual representation of icon colour in eye-controlled systems. (April 2022) - Ya-feng, Niu; Jin, Liu; Jia-qi, Cui; Wen-jun, Yang; Hong-rui, Zuo; Jia-xin, He; Lang, Xiao; Jia-hao, Wang; Guo-rui, Ma; Zi-jian, Han; Cheng-qi, Xue; Xiao-zhou, Zhou; et al.
Abstract: Given the wide application of eye-controlled systems, the target population is not only people with a physical disability. The importance of design is increasing; no matter where the eye-controlled system is to be applied, research on the interface needs to keep up with system development. Based on the analysis of the characteristics of eye movement, and the interaction of eye-controlled systems and visual design principles, the aim of this study was to explore whether a change in the colour of the interactive elements in an eye-controlled system will affect the efficiency of a user's visual search. Based on the actual needs of the eye-movement interaction process in the eye-controlled system, we developed an eye-controlled interaction system using Unity software. Based on this system, we investigated whether a change in the colour of the interactive elements in the eye-controlled system interface was related to search duration. The experimental data verified that changes in colour saturation and brightness affected users' search efficiency. When the saturation value of the icon colour was in the three ranges of 33% to 44%, 62% to 70, or 85% to 98%, reaction time was longest; the brightness value of the icon colour should be higher than 16%, and it is not recommended to be less than 5% under any circumstances. The experiment was combined with a questionnaire to quantitatively analyse participants' evaluation of the three types of feedback colours: reducing brightness, converting to the contrasting colour and converting to white. It was found that participants generally believed that the feedback form of reducing brightness was very natural, and the feedback form of converting to the contrasting colour was very clear. Moreover, it was found that participants of different ages had significant differences in the evaluation of feedback colour types. This study adds substantial evidence to the field of colour research in the visual representation of eye-controlled system interfaces.